Anolyte Solution Generated from Electrochemical Activation Process for the Treatment of Phenol - Zaulfikar, (2004)
Studies on the treatment of an aqueous solution of phenol using anolyte solution generated from electrochemical activation process were carried out. The aim of the studies is to investigate the effectiveness of anolyte solution in treating 100, 200, and 500 mg/l of phenol in water solution. Kinetic parameters, such as reaction rate constant (k) and order of reaction (n) should be studied to determine rate of degradation of phenol by anolyte solution. The treatment was carried out on batch experiment.